Utilization of Non-Timber Forest Products Based on Traditional Culture: A Case Study of Iban Dyeing in Sarawak, Borneo, Malaysia - Fujisawa, Natsuho; Nakashizuka, Tohru (Ethnobiology Letters, 2012)
In this brief report, we describe four plant species that Iban weavers use for dyes and six ingredients that they use in mordants. From September to November 2009, we interviewed four weavers and observed additional persons collecting and processing dye plants in three Iban villages whose names are Rumah Engkang, Rumah Ejon, and Rumah Nyawai. We also collected twenty-four plant vouchers which are deposited in the Sarawak Herbarium in the Forest Research Centre of Sarawak. The means by which Iban acquire dye materials varies by community and by individual weaver within each community. Generally, however, Iban collect plants when they are abundant in forests and easy to access and cultivate or, alternatively, they purchase plants that are scarce in the wild. Women use the yarns that they dye with plants to weave cloths.